(untitled) (World Bulletin of Management and Law, 2022)
In the lexicon of the Dari language, a terminological system related to the military field has emerged and is being used in practice. By itself, these military terms are used by the military and ordinary people, becoming a specific lexical layer of the language. The need to name new phenomena and concepts that appear in the life of society raises various issues in linguistics and, in particular, in terminology. Solving these problems will help to identify ways of formation and development of different lexical systems, and on this basis to correctly understand the laws of general development.